ПСИХОДИАГНОСТИК ТЕСТ ШАХС ХУСУСИЯТЛАРИНИ АНИҚЛАШ ВОСИТАСИ СИФАТИДА - Расулов, А.И. (SCIENCE and SOCIETY, 2018)
The article is devoted to the psychodiagnostic test aimed at personal qualities. The attention is focused on the standards of adaptation and evaluation of psychodiagnostic tests.
Keywords: personality; psychodiagnostics; psychodiagnostic test; adaptation; scales